Cytotoxic Necrotizing Factor 1 Downregulates CD36 Transcription in Macrophages to Induce Inflammation During Acute Urinary Tract Infections - Yang, Huan; Li, Qianqian; Wang, Changying; Wang, Jingyu; Lv, Junqiang; Wang, Lei; Zhang, Zhi-Song; Yao, Zhi; Wang, Quan (Frontiers in Immunology, 2018)
Urinary tract infections (UTIs) caused by uropathogenic Escherichia coli (UPEC) induce cystitis, pyelonephritis, and can cause kidney scarring and failure if inflammation is not under control. The detailed effects of cytotoxic necrotizing factor 1 (CNF1), the key UPEC toxin, on the pathogenicity of UPEC remain unclear. CD36 is an important scavenger receptor, responsible for pathogen and apoptotic cell clearance, and plays an essential role in host immune defense and homeostasis. Regulation of CD36 by bacterial toxins has not been reported. In this study, using a pyelonephritis mouse model, CNF1 was observed to contribute to increasing neutrophils and bacterial titers in infected bladder and kidney tissues, resulting in severe inflammation and tissue damage. CD36 expression in macrophages was found to be decreased by CNF1 in vitro and in vivo. We demonstrated that CNF1 attenuated CD36 transcription by decreasing expressions of its upstream transcription factors LXRβ and C/EBPα and their recruitment to the CD36 promotor. In addition, Cdc42 was found to be involved in CNF1-mediated downregulation of LXRβ. Our study investigated the pathogenesis of cnf1-carrying UPEC, which affected host innate immune defenses and homeostasis through regulation of CD36 in macrophages during acute UTIs.